Coinoculação de bactérias promotoras de crescimento em feijão-fava e feijão-comum - Ferreira, Linnajara de Vasconcelos Martins (2016)
A great number of bacterial species, especially those present in the rhizosphere, plays an important role on the growth and development of plants. This group of bacteria is often referred to as plant growth promoting rhizobacteria (RPCPs). Herein, two stud ies of inoculation and co -inoculation of RPCPs in common bean ( Phaseolus vulgaris) and lima bean (Phaseolus lunatus) were carried out. The first study aimed to genetically identify isolates of common bean nodules from Amazonian pasture soils, verifying their ability to nodulate as well as to promote bean growth when inoculated or co-inoculated with CIAT 899 (Rhizobium tropici). Two experiments were carried out under axenic conditions at the greenhouse using the Talisman common bean cultivar. The sequencing of the 16S rRNA gene showed predominance of the Pseudomonas genus in 35% of the sequenced strains. Other genera such as Rhizobium, Burkholderia, Pseudomonas, Variovorax, Xanthomonas and Bacillus were also identified, which demonstrates the great genetic diversity of bacterial strains under pasture systems with strains of the Bacillus and Pseudomonas genera. Those strains have great potential as plant growth promoters. The inoculation of the seven strains with CIAT 899 promoted a wide growth range in the different forms of nitrogen supply. The second study aimed at evaluating the effect of inoculation by strains of Bacillus, Paenibacillus, Burkholderia, and Pseudomonas – either individually or in combination with Rhizobium tropici – considering the potential for rhizoctoniosis biocontrol as well as the growth promotion in common bean and lima bean. Greenhouse experiments were carried out in axenic conditions using the Pérola common bean cultivar and creole seeds of lima bean. In the first stage of the exper iment the potential of 14 strains in the control of R. solani that was both individually inoculated and inoculated in conjunction with the CIAT 899 was assesed. For the second stage, strains were assessed for their ability to improve plant development in p lants growing in three different nitrogen supply media. The results demonstrated that the use of rhizobacteria combined with R. tropici synergistically contributes to growth development and control of rhizoctoniosis in lima bean and common bean. The mineral form of nitrogen can be replaced by the co-inoculation of CIAT 899 with the following plant growth promoting strains: UFLA 02-281, UFLA 02-286, UFLA 02-293 in the common bean culture. There was an increase in lima bean biomass when media was co-inoculated with the following strains: UFLA 02-286, UFLA 02-293, UFLA 04-195, UFLA 02-281 and UFPI B3-9.